1974
DOI: 10.1088/0022-3727/7/12/318
|View full text |Cite
|
Sign up to set email alerts
|

The abnormal glow discharge in mercury vapour and xenon

Abstract: Measurements have been made of the current-voltage characteristics of abnormal glow discharges in mercury vapour and xenon, both with a mercury cathode, over a pressure range from 0·5 to 15 mm Hg. Measurements have also been made of the cathode fall distance as a function of the voltage, but at low voltages only.A theoretical description is presented and is in good agreement with experiment. The main features of the theory are: at high current densities, the gas density increases towards the cathode as a resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…A better agreement may be expected if the movement of the spot is taken into account. This view was put forward by Holmes (1974), who calculated a power loss per unit area Ucon Ja=pCpT V/3. Here p is the specific mass, Cp the specific heat and V the spot velocity (see also von Engel and Robson 1957).…”
Section: Discussionmentioning
confidence: 99%
“…A better agreement may be expected if the movement of the spot is taken into account. This view was put forward by Holmes (1974), who calculated a power loss per unit area Ucon Ja=pCpT V/3. Here p is the specific mass, Cp the specific heat and V the spot velocity (see also von Engel and Robson 1957).…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the different treatment duration times, treatment doses differing by at least one order of magnitude were used. [23][24][25] …”
Section: Glow-discharge Plasma Treatmentmentioning
confidence: 99%
“…On the other hand, few theoretical investigations have been reported. One theory was proposed by Holmes (1974). His theoretical model for the arc cathode spot permitted a quantitative description of the parameters of the arc spot, and showed that values of the spot parameters calculated for mercury and copper cathode arcs agreed in part with experimental measurements.…”
Section: Introductionmentioning
confidence: 87%
“…Although these values are larger than our theoretical values, both values agree within an order of magnitude. Holmes (1974) proposed that the maximum radius of an arc root for which there is a solution to the equations derived theoretically by him was 9.1 X cm. His value was calculated assuming a constant current density ( J = 1.5 X lo6 A cm-2) and constant cathode-fall voltage (Vc = 7.7 V) over the whole arc current range.…”
Section: Molybdenum Anchormentioning
confidence: 99%
See 1 more Smart Citation